Fusion of tradition and modernity: Digital inheritance and sustainable protection of Kyrgyzstan’s intangible cultural heritage - Li, Kun; Yilihamu, Jiayina; Sarygulovna, Kasmalieva Anarkan (Edelweiss Applied Science and Technology, 2025)
Kyrgyzstan’s intangible cultural heritage (ICH), including oral epics, crafts, and rituals, faces threats from modernization, globalization, and insufficient policy support. This study explores the challenges of ICH transmission and proposes strategies for sustainable safeguarding through digital innovation, community collaboration, and transnational cooperation. Qualitative research was undertaken via literature review (30+ sources), semi-structured interviews (20 participants), and participatory observation in Bishkek and rural areas (2023–2024). Results: Key challenges include declining youth engagement, economic marginalization of traditional crafts, and fragmented policy implementation. Digital tools and transnational partnerships offer transformative potential but risk cultural dilution. A holistic safeguarding framework integrating legislation, education, community action, and technology is essential for preserving Kyrgyz ICH. Policymakers must prioritize cross-sectoral collaboration, digitization, and youth engagement to align with UNESCO’s goals for ICH sustainability.